BCOM, 10th Edition - Carol M. Lehman; Debbie D. DuFrene; Robyn Walker (Cengage Learning, 2019)
Learn business communications YOUR way with Lehman/DuFrene/Walker's BCOM, 10E from 4LTR Press. This inviting, easy-reference textbook and online digital learning support guide you through mastering today's business communication concepts and skills. Visually engaging chapters offer helpful study tools like Chapter Review Cards that consolidate review material into a ready-made study tool. BCOM's MindTap allows you to learn with the printed book or completely online, on your terms. Read or listen to the book and study with the aid of instructor notifications, flashcards and practice quizzes. When it's time to review, you can easily gather everything you've flagged or noted into a guide you organize. Track your scores so you know where to focus your efforts and stay motivated in reaching your learning and business communication goals.